MUC471 : Instrument II / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
This course focuses on individual instrument instruction in accordance to the student’s respective major and level of study. Students learn about playing techniques, performing skills and the stylistic interpretation of a variety of pieces. Students perform competently on their principal instrument.